2012
DOI: 10.1134/s0021364012010067
|View full text |Cite
|
Sign up to set email alerts
|

Generation of superthermal plasma flows in current sheets

Abstract: The profiles of the He II 3203 Å and He II 4686 Å spectral lines of helium ions have been detected and ana lyzed. Using these data, the processes of acceleration and heating of a plasma in current sheets that are formed in magnetic configurations with X type singular lines have been analyzed. The generation of plasma flows with energies of 400-1300 eV, which are much higher than the thermal energy of ions, has been revealed. The acceleration of the plasma induced by Ampere forces is likely spatially inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In the recent exper iments [53][54][55][56][57], the excitation of the Hall currents and the formation of the quadruple configuration of the longitudinal magnetic field were observed. Plasma acceleration and generation of suprathermal plasma streams were also demonstrated in [58][59][60]. Compar ison of thin CSs formed near the magnetic reconnec tion region in the Earth's magnetotail and in the labo ratory experiment was presented in [61].…”
Section: Introductionmentioning
confidence: 89%
“…In the recent exper iments [53][54][55][56][57], the excitation of the Hall currents and the formation of the quadruple configuration of the longitudinal magnetic field were observed. Plasma acceleration and generation of suprathermal plasma streams were also demonstrated in [58][59][60]. Compar ison of thin CSs formed near the magnetic reconnec tion region in the Earth's magnetotail and in the labo ratory experiment was presented in [61].…”
Section: Introductionmentioning
confidence: 89%
“…In the CSs, which are formed in He plasma, the ion temperature is (50-90) eV, whereas plasma jets gain much higher energies: from 400 to 1300 eV, depending on the initial conditions, see Figure 6 as an example (Kyrie et al 2012). It is suggested that plasma acceleration is more effective in the regions with lower plasma density, which are located at some distance from the CS midplane .…”
Section: Generation Of Plasma Jets In Current Sheetsmentioning
confidence: 99%
“…Magnetic energy accumulated in the vicinity of the metastable current sheet can be transformed into thermal energy and into the energy of high-speed flows of plasma [18][19][20]. Plasma is accelerated along the surface of the current sheet mainly under the action of the Ampère forces that are initially directed from the central region of the sheet to its edges on both sides [11,21].…”
Section: Introductionmentioning
confidence: 99%